Overnutrition-induced gout: An immune response to NLRP3 inflammasome dysregulation by XOD activity increased in quail - Wu, Hao; Wang, Yu; Ren, Zhixin; Li, Yaolei; Huang, Jingjian; Lin, Zhijian; Zhang, Bing (Frontiers in Immunology, 2022)
Background Gout is a progressive metabolic disease closely related to hyperuricemia and urate deposition, with an increasing prevalence and incidence across the globe. Recent studies have shown that the pathological process of gout includes two stages: asymptomatic hyperuricemia and MSU crystal deposition. However, the immune response during the development of hyperuricemia to gouty arthritis is not fully elucidated. Methods Thus, an overnutrition-induced whole-course gout model was established to clarify the immune response and pathological changes in the development from hyperuricemia to gouty arthritis. The quails without urate oxidase were used as experimental animals. And we confirmed that uric acid metabolic targets were changed when quails were in the asymptomatic hyperuricemia stage. Results When the quail showed gout symptoms, the NLRP3 inflammasome was activated, and the expressions of IL-1β, TNF-α, IL-6, IL-8, and IL-18 were significantly increased. The relationship between the uric acid metabolism target and the NLRP3 inflammasome may be the critical immune response between hyperuricemia and gouty arthritis. Our data showed that, in the process of gout disease, the expression of xanthine oxidase (XOD) has been increasing, which increases the level of uric acid, disrupts the balance of oxidative stress, generates a large amount of ROS, activates the NLRP3 inflammasome, and release IL-1β. Treatment with the XOD inhibitor can reduce uric acid, restore the body’s degree of peroxidative damage and antioxidant capacity, and inhibit NLRP3 inflammasome and IL-1β. In vitro, we extracted and identified primary fibroblast-like synoviocytes (FLS) from quail for the first time. Stimulating FLS with uric acid also caused ROS release and NLRP3 inflammasome activation. However, treatment with an XOD inhibitor prevented all these responses in FLS. Conclusion Our results indicate that the immune response between the uric acid metabolism target XOD and NLRP3 inflammasomes plays a crucial role in developing hyperuricemia to gouty arthritis, and inhibition of both XOD and NLRP3 inflammasomes may be an effective treatment for avoiding the development of asymptomatic hyperuricemia to MSU crystal deposition. Meanwhile, this study also provides an advantageous animal model for pathological mechanisms and research and development drugs for gout.